Poor family relationships in adolescence as a risk factor of in-patient somatic care across the life course: Findings from a 1953 cohort - Susanne Alm; Sara Brolin Låftman; Hannes Bohman (Elsevier, 2021)
Background: Prior research has shown that poor family relations during upbringing have long-term detrimental effects on mental health. Few previous studies have, however, focused on somatic health outcomes and studies rarely cover the life span until retirement age. The aims of the current study were, firstly, to examine the association between poor family relationships in adolescence and in-patient somatic care across the life course whilst adjusting for confounders at baseline and concurrent psychiatric in-patient care; and secondly, to compare the risks of somatic and psychiatric in-patient care across the life course. Methods: Prospective data from the Stockholm Birth Cohort study were used, with 2636 participants born in 1953 who were followed up until 2016. Information on family relationships was collected from the participants' mothers in 1968. Annual information on in-patient somatic and psychiatric care was retrieved from official register data from 1969 to 2016. Results: Poisson regressions showed that poor family relationships in adolescence were associated with an increased risk of in-patient somatic care in mid- and especially in late adulthood (ages 44-53 and 54-63 years), even when controlling for the co-occurrence of psychiatric illness and a range of childhood conditions. No statistically significant association was observed in early adulthood (ages 16-43 years), when controlling for confounders. These findings are in sharp contrast to the analyses of inpatient psychiatric care, according to which the association with poor family relations was strongest in early adulthood and thereafter attenuated across the life course. Conclusion: Poor family relationships in adolescence are associated with an increased risk of severe consequences for somatic health lasting to late adulthood even when controlling for confounders including in-patient psychiatric care, emphasising the potentially important role of early interventions.